"I Wanted to Raise My Hand and Say I'm Not a Feminist": College Men's Use of Hybrid Masculinities to Negotiate Attachments to Feminism and Gender Studies. Issue 3 (October 2017) - Schmitz, Rachel M.; Haltom, Trenton M.
Using a hybrid masculinities framework, we qualitatively analyzed 15 college men's experiences with feminism and gender scholarship in Women's and Gender Studies (WGS) courses. Men described adopting particular strategies of discourse in their social interactions to manage varied reactions to feminism and gender studies. As a way of justifying their choice of academic study, these men also learned to navigate social relationships by highlighting or downplaying their own masculinity (i.e., creating or deconstructing a hybrid masculinity). Finally, men reconciled the multiple meanings of feminism and WGS studies by drawing from dominant cultural norms and expectations in attempts to make sense of the incongruence of men studying feminism. Implications for future research and college campuses and educators are considered.